ORGANIZING PRACTICAL EDUCATION COURSES ON SEWING PROFESSION FOR STUDENTS WITH DISABILITIES (Multidisciplinary Journal of Science and Technology, 2024)
This article describes the procedure, importance and effectiveness of organizing practical education training sessions on the secrets and profession on sewing for students with disabilities.